1994
DOI: 10.1246/bcsj.67.3334
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Ethylbenzene over Spinel Oxides

Abstract: NiCr2O4, ZnCr2O4, CuCr2O4, CuAl2O4, and CuFe2O4 were prepared and characterized by XRD, DRS, and IR and by measurements of surface area, acidity, and electrical conductivity. XRD analysis indicates, that chromites, aluminate, and ferrite have normal, partially inversed, and inversed spinel structure, respectively. Electrical conductivity measurements show the existence of pair localized ions which are positive in chromites and negative both in aluminate and ferrite. The catalytic activity of chromites and alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…Uma outra amostra, à base de ferrita de alumínio, foi preparada usando o método proposto por Jebarathinan e colaboradores 28 (Amostra FA2). Uma solução contendo nitrato de ferro e de alumínio (Fe/ Al (molar)=1), foi aquecida a 60 ºC e, a esta, foi adicionada (ainda quente) uma solução de hidróxido de amônio 5%, gota a gota, sob agitação constante, mantendo-se o pH em 6,2.…”
Section: Parte Experimentalunclassified
“…Uma outra amostra, à base de ferrita de alumínio, foi preparada usando o método proposto por Jebarathinan e colaboradores 28 (Amostra FA2). Uma solução contendo nitrato de ferro e de alumínio (Fe/ Al (molar)=1), foi aquecida a 60 ºC e, a esta, foi adicionada (ainda quente) uma solução de hidróxido de amônio 5%, gota a gota, sob agitação constante, mantendo-se o pH em 6,2.…”
Section: Parte Experimentalunclassified
“…One of these nanomaterials is nickel chromite (NiCr 2 O 4 ). It was found that nickel chromite with spinel structure is an important transitionmetal oxide owing to its specific electrical, magnetic, and catalytic properties [6] as well as potential applications, including catalytic materials, electronic apparatus, gas sensors, chemical industrial fields, and pigments [7][8][9][10]. NiCr 2 O 4 has a spinel-like structure [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nanosized ferrites with uniform particle size and narrow size distribution are one of the most important ceramic materials widely used as targeted drug delivery, ferrofluids, medical imaging and other biomedical applications, magnetic data storage as well as giving an excellent performance as catalyst or catalytic support for many chemical reactions [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recent interest in the study of several spinel-type ferrites is in terms of the synthesis of their nanoparticles at low temperatures by different techniques, in view of the potential applications of these nanosized magnetic materials in different technological areas, as well as to study the intriguing magnetic properties of the nano-ferrite materials [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%